Introduction: University Autonomy - Kirsten Roberts Lyer; Ilyas Saliba; Janika Spannagel (University Autonomy Decline: Causes, Responses, and Implications for Academic Freedom, 2023)
Over the past ten years, both academic freedom and university autonomy have been in decline in many countries around the globe, as analyses of the Academic Freedom Index (AFI) data show. This introductory chapter establishes the purpose and scope of the book and introduces the AFI dataset as one of its key resources. On this basis, the chapter maps the global state of university autonomy, provides an empirical assessment of global trends in components of academic freedom, and points to the interrelation of university autonomy and democracy levels, which will be addressed in more detail in later chapters.
Additional information: The publication of the open access book "University Autonomy Decline: Causes, Responses, and Implications for Academic Freedom" was funded by the Open Societies Foundation and the Open Access Publishing Fund of the Leibniz Association.
Keywords: 330